Analysis of the IAEA benchmark on heat transfer in a 4 × 4 rod bundle with mixing grid. (May 2018) - Bieder, Ulrich; Costa, Delphine
Highlights: CFD analysis of the flow in a partly heated rod bundle. Analysis of different thermal boundary conditions. Comparison of the flow field to experimental results. Comparison of temperature profiles to experimental results. Abstract: The IAEA is organizing a Coordinated Research Project (CRP) on the application of Computational Fluid Dynamics (CFD) for nuclear reactor design. Within this CRP, an open benchmark is organized on fluid mixing in rod bundles. KAERI has offered precise experimental data of the velocity field downstream of a mixed twist/split type mixing grid. Additionally, temperature measurements in various axial and azimuthal locations of a partly heated rod were made available by KAERI. The experimental set up consists of a 2000 mm long bundle of 4 × 4 rods with pitch to diameter ratio of 1.35, placed in a square housing of 142 × 142 mm. Each rod has a diameter of 25.4 mm. The mixing grid is located at 2/3 height of the channel with 5 spacer grids located upstream and 3 downstream of the mixing grid. These experiments are analysed with the TrioCFD code. Turbulence is treated with the RANS approach by using a non-linear eddy viscosity model. The comparison of measured and calculated mean velocity fields is presented. Measured profiles of velocity mean values were calculated correctly for the central sub-channel and the gap of rod-to-rod both close and far from the mixing grid. The measured temperature is underestimated by the calculations, on one hand due to the localization of the thermocouples inside the wall of the rod and on the other hand due to the used thermal boundary condition called "imposed heat flux". A first order correction procedure helps to understand the detected discrepancy between experiment and calculation.